Adsorptivities of Extremely High Surface Area Activated Carbon Fibres for CH and H - A. Rejifu; H. Noguchi; T. Ohba; H. Kanoh; F. Rodriguez-Reinoso; K. Kaneko (Adsorption Science & Technology)
Activated carbon fibres with extremely high surface areas (ACFs) were prepared by CO 2 re-activation using pitch-based ACFs having an original surface area of 1730 m 2 /g. The highest surface area of the re-activated ACFs was 2930 m 2 /g as determined from an α S -plot analysis of the nitrogen adsorption isotherm measured at 77 K. The ACF with the highest surface area showed excellent adsorptivity towards supercritical CH 4 and H 2 . The amounts of CH 4 and H 2 adsorbed were enhanced by 52% and 30%, respectively, as a result of re-activation.